MODAL SOSIAL MASYARAKAT DALAM PENGELOLAAN TEMBAWANG DI DESA PALOAN KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - anasia melia; emi roslinda; hari prayogo (Universitas Tanjungpura, 2022)
The management of tembawang by the community in Paloan Village has been carried out for generations. It is important to know social capital in the management of tembawang because tembawang is still maintained by the community even though commercially it does not provide anything significant to people's income. This study aims to examine and assess the characteristics of individuals in the community, examine the condition of social capital community in tembawang management, measure and analyze the relationship between individual characteristics and the elements of social capital, between social capital and its constituent elements and between social capital and tembawang management. in Paloan Village. This research was conducted by field observations, direct interviews with respondents and assisted by questionnaires that have been prepared as well as literature studies by collecting secondary data from various agencies and the results of previous studies related to the research. The level of social capital of the community was analyzed using the value interval equation. While the relationship of social capital was analyzed using the Sperman Rank coefficient test. The results showed that the level of social capital of the Paloan Village community was in the